The right to information from the point of view of legal theory, international law and international relations - Шминдрук, Ольга Федорівна; Шминдрук, О. Ф.; Shmyndruk, Olha F.; Чувакова, Ганна Михайлівна; Чувакова, Г. М.; Chuvakova, Hanna M.; Рязанов, Михайло Юрійович; Рязанов, М. Ю.; Riazanov, Mykhailo Yu.; Петренко, Наталія Дмитрівна; Петренко, Н. Д.; Petrenko, Nataliia D.; et al. (Florencia : Editorial Primmate S. A. S., 2024)
The investigation explores the relationship between mediation and the right to a fair trial, examining whether mediation is a legal heritage or an anomaly within the legal sphere. The study analyzes the legal framework of mediation in Ukraine and other countries, along with international standards. It investigates the impact of mediation on the right to a fair trial and its role in Ukraine's European integration process. The methodology includes policy analysis, empirical research, and comparative methods. The findings suggest that mediation is a valuable addition to the legal system, promoting efficient dispute resolution and reducing the burden on courts. However, upholding clear standards and principles is crucial to ensure the protection of participants' rights and maintain the right to a fair trial. The research concludes that mediation can coexist harmoniously with traditional judicial processes, contributing to a more effective and just legal system.
Shmyndruk О. The right to information from the point of view of legal theory, international law and international relations / О. Shmyndruk, H. Chuvakova, M. Ryazanov et al. // Amazonia Investiga. – Florencia : Editorial Primmate S. A. S., 2024. – 13(79). - P. 165–176. URL: https://doi.org/10.34069/AI/2024.79.07.13
Keywords: mediation; right to a fair trial; alternative dispute resolution; legal system; legal heritage